Three women pose with a large poster - Rowe, Martin:::Creator::::::::::::
Photograph shows three women posing with a large poster for an YWCA World Fellowship Benefit. One woman who is wearing a hat has posed in front of the poster with her arms raised up and out. The sign reads: "'An Italian St[raw Hat]. Sponsored by San Jose YWCA. Produced by San Jose Theater Guild. World Fellowship Benefit. Friday, June 21, 1963. Civic Auditorium. Tickets $2.00. Buy your tickets today!"